2010
DOI: 10.1364/oe.18.003226
|View full text |Cite
|
Sign up to set email alerts
|

On-chip temperature compensation in an integrated slot-waveguide ring resonator refractive index sensor array

Abstract: We present an experimental study of an integrated slot-waveguide refractive index sensor array fabricated in silicon nitride on silica. We study the temperature dependence of the slot-waveguide ring resonator sensors and find that they show a low temperature dependence of -16.6 pm/K, while at the same time a large refractive index sensitivity of 240 nm per refractive index unit. Furthermore, by using on-chip temperature referencing, a differential temperature sensitivity of only 0.3 pm/K is obtained, without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 20 publications
0
61
1
Order By: Relevance
“…The results are shown in Table 1. For these values of the sensitivity, (14) implies that the relative change in the resonant wavelength is It should be noted that the gain in the sensitivity for a dual core design is not that significant in order to justify the complexity of the design and the manufacturing challenges that entails. Therefore, it is suggested that in most practical situations, the design of choice would be a single core waveguide with dimensions for the core dimensions provides better sensitivity than the dual core design as far as the behavior of the system as biosensor is considered.…”
Section: Simulations Results and Discussion Regarding Design Optimimentioning
confidence: 99%
“…The results are shown in Table 1. For these values of the sensitivity, (14) implies that the relative change in the resonant wavelength is It should be noted that the gain in the sensitivity for a dual core design is not that significant in order to justify the complexity of the design and the manufacturing challenges that entails. Therefore, it is suggested that in most practical situations, the design of choice would be a single core waveguide with dimensions for the core dimensions provides better sensitivity than the dual core design as far as the behavior of the system as biosensor is considered.…”
Section: Simulations Results and Discussion Regarding Design Optimimentioning
confidence: 99%
“…Sensor sensitivity can be improved by a proper slot region design, which allows for a complete filling of the slot region by the biological fluid [44]. Recent results [76] have shown that a proper slotted ring resonator design allows for eliminating sensor response temperature dependence. This is an important advantage with respect of previously proposed sensor configurations.…”
Section: Advantages Of Label-free Optical Detectionmentioning
confidence: 99%
“…The measurements described in the next subsection were made over 7 K operating window, without external temperature control and individual sensor calibration. This is further described elsewhere [18].…”
Section: Sabio Nanophotonic Sensorsmentioning
confidence: 99%